MINIMISING STUDENTS’ ERRORS IN WRITING PROCEDURE TEXT: WHAT STRATEGIES DO TEACHERS EMPLOY? - Iqlima Sarah Kismawati,; Siti Nur’aini,; Faiza Hawa, (JOEL: Journal of Educational and Language Research, 2023)
This study aimed at finding out errors students made when writing procedure texts and strategies the teachers employed to overcome the errors . This study used a qualitative method. This study was conducted at SMAN 01 Bae Kudus. Researchers employed observations, interview to teachers, and documentation to gather data. The study revealed that students made errors when writing procedure texts; those are interlanguage, intralingual, spelling, grammar, and punctuation. To minimise the errors,, the teacher used the "jembatan keledai" method and the Duolingo program. The success rate for using this strategy to minimize student errors is 50% for the Duolingo program and 70% for “jembatan keledai